The litigation state : public regulation and private lawsuits in the United States - Farhang, Sean, 1966- (Princeton studies in American politics., 2010)
Of the 1.65 million lawsuits enforcing federal laws over the past decade, 3 percent were prosecuted by the federal government, while 97 percent were litigated by private parties. When and why did private plaintiff-driven litigation become a dominant model for enforcing federal regulation? The Litigation State shows how government legislation created the nation's reliance upon private litigation, and investigates why Congress would choose to mobilize, through statutory design, private lawsuits to implement federal statutes. Sean Farhang argues that Congress deliberately cultivates such private.